The Iberian ambition of a Duke of Burgundy: Philip the Handsome and the royal treasury in the Crown of Castile (1502-1506). - Gálvez Gambero, Federico (Taylor & Francis, 2022)
Philip the Handsome, the first Habsburg king of Castile, ruled briefly, in tandem with his wife except for the final three months of his reign, from the death of Isabella I in November 1504 to his own demise in September 1506. The problems, but also the potential, of the dynastic union of Castile and the Low Countries were clear from the time he took his oath as a prince in 1502. Castile’s royal treasury, which entered a severe crisis in 1503, was to become, owing to its political importance and its role as a major source of revenue, a primary arena for these dynastic interactions.
The Version of Record of this manuscript has been published and is available in Journal of Medieval History 2022 https://www.tandfonline.com/doi/abs/10.1080/03044181.2022.2076724 Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/21305
Keywords: Castilla (Reino) - Política fiscal; Felipe Rey consorte de Juana I, Reina de Castilla; Crown of Castile; Ferdinand the Catholic; Philip the Handsome; Public finance; Fiscal systems; Public debt